Trust and Occupational Safety Behavior Related to Decompressive Diseases on Bajo Ethnic Divers - Mallapiang, Fatmawaty; Syarfani, Syarfani; Aeni, Syahratul (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2023)
The total area of Indonesian waters exceeds the land area, so the sea becomes one of the land community's livelihoods. Majority of the Bajo ethnic community work as traditional diver fisherman. This study examined trust community and their occupational safety and health behavior related to decompression sickness in Ethnic Bajo Divers. This type of research was qualitative, using an ethnographic study approach. Key informants in this study were ethnic Bajo divers who experienced and did not have paralysis. Data were collected through observation, in-depth interviews, documentation, sources, methods, and time triangulation. The beliefs and traditions of ethnic Bajo divers were related to safety and prevention. Decompression was before diving, asking for safety from the Almighty Creator by saying greetings and basmalah and praying before diving, which was a form of permission to The Guardian of the Sea. The Personal Protective Equipment that must be used were glasses (wooden/traditional glasses or glasses Ventara/modern). Decompression was understood as a disease cold with symptoms of cramps in the lower limbs obtained the result of diving for a long time at a certain depth to find seawater that was yellow like oil and very cold. Bajo tribe divers perform decompression treatment based on local wisdom and instill occupational health and safety behaviors and convince themselves by praying and saying basmallah before diving.